Hardware and software advances in capsule endoscopy - Beg, Sabina (2019)
Capsule endoscopy was introduced in 2000 and has since become the investigative modality of choice for mucosal diseases of the small bowel. This innovative device, which comprises of imaging components encased within a pill-sized capsule, allows for non-invasive examination of the small bowel. The aim of this thesis is to evaluate advances in capsule endoscopy which have the potential to extend and improve the practice of this tool.